Aplicativo Verific.AI-automatização de checagem de links de notícias no combate ao ecossistema da desinformação. - Souza, Alice Cristiny Ferreira de (2019)
The computer, the internet, and digital social networking sites have broken the paradigm of mass communication. With them, information became the strategic resource of economics, and emotion took the place of reason. In this context, the present work studies a new ecosystem of information disorders, which creates an atmosphere of fragility in the public debate. This dissertation presents the development, testing and data analysis experience of the Verific.ai application prototype, an automation tool for checking news links available for Android system. The app applies the technique of data mining from the definition of truth criteria and falsity of news in the digital environment. The data are presented in light of the exploratory descriptive analysis performed through the reception of 373 links between october 16 and 28, 2018, the Brazilian electoral period, as well as based on the discussions raised by Alvin Toffler, Manuel Castells, Pierre Levý, Henry Jenkins, David Harvey and Clay Shirky. As a result, the study evidenced that the news transmitted by traditional media in the digital environment are disregarded, as well as increasing evidence of the space of news consumption in digital social networks..